2017
DOI: 10.1111/ejn.13664
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic analysis of contextual fear conditioned rats reveals dynamic modifications in neuron and oligodendrocyte protein expression in the dentate gyrus

Abstract: Contextual memory is an intricate process involving synaptic plasticity and network rearrangement. Both are governed by many molecular processes including phosphorylation and modulation of protein expression. However, little is known about the molecules involved in it. Here, we exploited the advantages of a quantitative proteomic approach to identify a great number of molecules in the rat dentate gyrus after a contextual fear conditioning session. Our results allowed us to highlight protein expression patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 76 publications
2
8
0
Order By: Relevance
“…6C). These results are consistent with a role for cFC in promoting plasticity-related changes in palmitoylation that are more broadly distributed across different cell types in the hippocampus ( 22 , 27 , 28 , 30 33 ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…6C). These results are consistent with a role for cFC in promoting plasticity-related changes in palmitoylation that are more broadly distributed across different cell types in the hippocampus ( 22 , 27 , 28 , 30 33 ).…”
Section: Resultssupporting
confidence: 85%
“…No statistical methods were used to predetermine sample size. The sample size for the proteomic screen was based on previous work ( 9 , 22 , 23 , 62 ). No randomization was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps myelin-based mechanisms first need to decrease to allow a subsequent increase in oligodendrocyte changes that would be needed to stabilize newly established connectivity. In line with this idea, a decrease in myelin proteins was reported by proteomic analysis of the dentate gyrus 24 h after contextual fear conditioning in mice (Houyoux et al, 2017). If our hypothesis is correct, it is possible that a delayed wave of oligodendrocyte transcript upregulation in the PL cortex may take place to support systems consolidation.…”
Section: Discussionsupporting
confidence: 75%
“…The higher expression in MOs is of interest, since myelin is known to stabilize synaptic networks, 398 and oligodendrocyte-related proteins have been shown to be modified in the rat dentate gyrus 399 during contextual fear conditioning (Houyoux et al, 2017). Moreover, microglia has been shown to 400 participate in cued fear conditioning (Parkhurst et al, 2013), and microglial acid sensing has been 401 shown to participate in carbon dioxide-evoked fear (Vollmer et al, 2016).…”
Section: /23mentioning
confidence: 99%